OPTIMASI METODE FLOTASI SENTRIFUS MENGGUNAKAN LARUTAN ZnSO₄, MgSO₄, DAN NaCl BERDASARKAN KONSENTRASI LARUTAN DAN LAMA PENGAPUNGAN - Alma Tiara Rahayu; Aldi Pratama; M. Wahyu Setiawan; Ma'rifatussolihat Ma'rifatussolihat; Nurul Azmah Nikmatullah (Poltekkes Kemenkes Pakassar, 2023)
In Indonesia, helminth infection is one of the diseases with a fairly large number. Soil Transmitted Helminth (STH) is the transmission of helminth infection through the soil. Examination of feces is carried out to diagnose helminth infections by finding infective eggs or larvae. Deworming analysis can be done quantitatively or qualitatively. The flotation, sedimentation and native (direct slide) method is a qualitative worm infection examination method to detect intestinal parasites, while the Kato-Katz method is a quantitative method of detecting helminth infections. Purpose: to find out the optimal concentration and duration of flotation in the flotation method using solutions of ZnSO, MgSO and NaCl. The method used is the centrifugal flotation method. The samples were screened and 12 positive samples were obtained. Results: found egg type of worm Ascaris lumbricoides with fertile, infertile and decorticated forms. At a concentration of 33% 10 minutes, a solution of ZnSO 53 eggs was obtained, MgSO 16 eggs, NaCl 10 eggs while 20 minutes ZnSO 29 eggs, MgSO 39 eggs, NaCl 19 eggs were obtained. At a concentration of 43% time 10 minutes, ZnSO 29 eggs were obtained, MgSO 17 eggs, NaCl 11 eggs while a time of 20 minutes was obtained ZnSO 34 eggs, MgSO 26 eggs, NaCl 1 egg. Conclusion: the optimal concentration and flotation time in ZnSO solution is a concentration of 33% with a time of 10 minutes, mgSO solution with a concentration of 33% for 20 minutes, and a NaCl solution with a concentration of 33% for 20 minutes.